Model Perencanaan Ulang Drainase Untuk Mengurangi Genangan: Studi Kasus Di Perumahan Taman Griya Asri Cilebut, Kabupaten Bogor: Drainage Redesign Model To Reduce Influencing: A Case Study In Taman Griya Asri Cilebut Housing, Bogor Regency - Diyanti; Supomo, Fani Yayuk; Qodriah, Hamidah Nur (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Taman Griya Asri Cilebut housing complex, Bogor Regency, often experiences flooding due to high rainfall and inadequate drainage capacity. This study aims to redesign the drainage system, including calculating the planned flood discharge and determining the channel dimensions. The algebraic method is used for hydrological analysis because the catchment area is less than 500 km². The results of the study show that the planned flood discharge for a 5-year return period for secondary and tertiary channels varies between 0.02 m³/s to 0.39 m³/s. The redesign produces appropriate channel dimensions, for example tertiary channel 2 (h=0.5 m, b=0.4 m), tertiary 3 (h=0.6 m, b=0.8 m), and tertiary 4 (h=0.6 m, b=0.5 m) with a square shape using U-Ditch Precast. This redesign is expected to reduce flooding in the housing complex.